Application of CEDAW in Domestic Violence Cases in Indonesia: Case Study of Domestic Violence against Venna Melinda - Gunawan Yordan; Ruqmana Kundarti (SHS Web of Conferences)
Domestic violence is a form of human rights violation. Even though domestic violence has been prohibited, this kind of violence still often occurs in Indonesia. On Sunday, January 8, 2023, Venna Melinda experienced an incident of domestic violence committed by her husband, Ferry Irawan, resulting in a nose injury. This normative juridical research was conducted through a literature review using a legal framework and then evaluated using descriptive analytical methodology. Regarding the domestic violence faced by Venna Melinda, it should be noted that although CEDAW does not specifically address domestic violence, it requires member states to enact laws that address all types of discrimination against women, including domestic violence. Indonesia’s ratification of CEDAW shows Indonesia’s dedication to eliminating gender-based discrimination, which was transformed by the enactment of the PKDRT Law. The police have resolved the domestic violence case involving Venna Melinda so that the perpetrator received a criminal sentence from the judge. However, the Domestic Violence Law in Indonesia still has shortcomings in its regulation, so the handling of domestic violence situations is not optimal. Therefore, the author believes that the PKDRT Law has not effectively implemented CEDAW’s directives to eliminate gender-based discrimination against women. Based on the author’s point of view, the Domestic Violence Law needs to be revised, and its implementation should be improved as required by CEDAW.